2019
DOI: 10.1111/jasp.12629
|View full text |Cite
|
Sign up to set email alerts
|

How green defaults promote environmentally friendly decisions: Attitude‐conditional default acceptance but attitude‐unconditional effects on actual choices

Abstract: Defaults (i.e., options that become effective without an active choice) have been found to be powerful tools to influence decision‐making in a range of behavioral domains. However, seemingly conflicting assumptions have been expressed regarding the interplay of defaults with individual attitudes. Whereas some expect attitude‐conditional effects (i.e., a statistical default‐by‐attitude interaction), others assume an attitude‐unconditional effectiveness of defaults (i.e., statistically additive effects). Integra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 65 publications
5
20
0
Order By: Relevance
“…Fairly recently and in contrast to common practice, Kaiser and colleagues have come to reinterpret their measure of self-reports of past environmentally protective behavior (the General Ecological Behavior [GEB] scale; e.g., Kaiser, 1998;Kaiser & Wilson, 2000 as a measure of environmental attitude (see, e.g., Kaiser et al, 2007Kaiser et al, , 2010Kaiser et al, , 2013. In several experiments and in contrast to studies employing more traditional measures (see, e.g., Bickman, 1972), their compound measure of "environmental attitude," consisting of behavioral self-reports, was found to reliably account for manifest pro-environmental behavior: the demand for resources in a commons dilemma game (Kaiser & Byrka, 2015), the proportion of vegetarian lunches (Kaiser et al, 2020), the choice of CO2-optimal routes (Taube et al, 2018), and the proportion of green products (Taube & Vetter, 2019).…”
Section: Self-reports Of Pro-environmental Behaviorsmentioning
confidence: 85%
“…Fairly recently and in contrast to common practice, Kaiser and colleagues have come to reinterpret their measure of self-reports of past environmentally protective behavior (the General Ecological Behavior [GEB] scale; e.g., Kaiser, 1998;Kaiser & Wilson, 2000 as a measure of environmental attitude (see, e.g., Kaiser et al, 2007Kaiser et al, , 2010Kaiser et al, , 2013. In several experiments and in contrast to studies employing more traditional measures (see, e.g., Bickman, 1972), their compound measure of "environmental attitude," consisting of behavioral self-reports, was found to reliably account for manifest pro-environmental behavior: the demand for resources in a commons dilemma game (Kaiser & Byrka, 2015), the proportion of vegetarian lunches (Kaiser et al, 2020), the choice of CO2-optimal routes (Taube et al, 2018), and the proportion of green products (Taube & Vetter, 2019).…”
Section: Self-reports Of Pro-environmental Behaviorsmentioning
confidence: 85%
“…That is, across the behavioral domains of healthy eating and sustainability, and thus across pro-self and pro-social nudges, we found that goal strivings and autonomous motivation had a significant main effect on the behavior of interest. This corroborates findings from studies on the role attitudes in nudges' effectiveness (Kaiser et al, 2020;Kuhn et al, 2021;Taube & Vetter, 2019;Vetter & Kutzner, 2016), which have also revealed main effects only on behavioral outcomes. Controlled motivation did not affect our behavioral outcomes in Study 1 and 3, while it significantly predicted sustainable behavior in Study 2, but with negligible predictive power and little practical significance.…”
Section: Discussion Studysupporting
confidence: 89%
“…However, some research has been done to examine the impact of attitudes on nudge effectiveness, mostly in the realm of sustainable behavior (e.g., green electricity uptake or organic food choices). These studies have consistently revealed that default nudges and attitudes independently predict behavioral outcomes (Kaiser, Bernauer, Sunstein, & Reisch, 2020;Kuhn, Ihmels, & Kutzner, 2021;Taube & Vetter, 2019;Vetter & Kutzner, 2016). Thus, current evidence suggests that defaults and attitudes have distinct and independent effects on behavior.…”
Section: The Role Of Motivationmentioning
confidence: 74%
See 1 more Smart Citation
“…These authors suggested that research should look at interactions between those two types of variables instead of studying them separately (see also Guagnano et al, 1995). Although the recommendation to explore the interaction between personal and situational variables was published more than 20 years ago, we could locate only a few published studies integrating personal variables and situational factors (see, for example, Taube and Vetter, 2019 for the same question on defaults), and none of them tested the interaction of environmental attitudes and prompts on subsequent ecological behavior. The present study addresses this gap by examining the extent to which individuals' environmental attitudes interact with situational prompts to induce energy-saving behavior.…”
Section: Introductionmentioning
confidence: 99%